Gastric ciliated metaplasia. A study of 3406 gastrectomy specimens from dwellers of the Atlantic and the Pacific basins. Issue 6 (25th May 2005) - Rubio, C A; Nesi, G; Zampi, G C; de Ruiz, P A; Jessurun, J; Jónasson, J; Hojman, R; Kogan, Z; Antonioli, D; Miller, M L; Hirota, T; Itabashi, T; et al.
Abstract : Background: Ciliated cells in gastrectomies from patients dwelling in the Pacific and Atlantic basins have been reported previously. Aim: To compare all the results in an attempt to explain the findings. Methods: Sections from 3406 gastrectomies were reviewed: 1966 and 1440 from the Atlantic and Pacific basins, respectively. Ciliated cells and intestinal metaplasia (IM) were recorded; IM was classified into focal or extensive IM. The total number of sections/gastrectomy was noted. Results: In the Atlantic basin, 5% of specimens had ciliated metaplasia (CM); it was more frequent in intestinal carcinoma (IC; 9%) than diffuse carcinoma (DC; 3%) or miscellaneous gastric diseases (MGD; 3%). In the Pacific basin, the frequency of specimens with CM was 29%: it was more frequent in IC (43%) than in DC (16%) or MGD (10%). The difference between the frequency of CM in specimens with IC or with DC/MGD in the Atlantic and the Pacific basins was significant (p ⩽ 0.05). The presence of CM was influenced by age and the extent of IM in both basins, but not by sex or the number of sections investigated. Conclusions: CM—apparently an independent microscopic marker—was significantly higher in the Pacific than in the Atlantic basin. Environmental carcinogens involved in the evolution of IM and IC seem to be implicated in gastric ciliogenesis. Carcinogens that differ in nature and/or in strength in both basins might activate the latent natural genes encoding ciliated processes in gastric cells in patients subsequently developing gastric carcinoma, more notably of intestinal type.